The Effect of Job Satisfaction on Employee Performance Through Employee Involvement as Mediator Variables at Snack Food Distributors in Surabaya, Sidoarjo, and Gresik - Aristotelin, Ronald (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to analyze the performance, job satisfaction, and employee engagement in theretail distributor. The main theory and previous researchers used in this study are Performance by Na-Nanet al., (2017), Employee engagement by Schaufeli, Salanova, González-Romá, and Bakker (2002) and Jobsatisfaction by Spector (1997). The method used in this research is Structural Equation Modeling withPartial Least Square. The program used is SmartPLS 3.3.3. This research was conducted in a snack foodretail distributor company located in Surabaya, Sidoarjo and Gresik with a sample of one hundred and tenrespondents. The results of this study are job satisfaction has a significant but not significant effect onemployee performance, employee involvement has a significant effect on employee performance, jobsatisfaction has a significant effect on employee engagement and employee involvement is the variable thatmediates job satisfaction on employee performance.